Development of Teacher’s Professional Competence through Action Research as a Form of Professional Development - Janka Ferencová; Ivana Pirohová; Valentina Šuťáková; Monika Miňová (Acta Paedagogica Vilnensia)
Action research serves as a significant tool for the professional development of teachers, the enhancement of educational practice, and the advancement of student learning. This review study aims to provide an empirically grounded perspective on action research as a means of stimulating the development of teachers’ professional competence. Drawing upon the analysis of 28 empirical studies from the Scopus, WoS, EBSCO, ProQuest, and Science Direct databases over the past five years, the study identifies the contributions of action research to the development of both core and key professional competences among teachers. The findings confirm that action research not only supports the expansion and deepening of teachers’ knowledge base but also fosters the development of their key professional competences which are vital for effectively addressing the challenges of pedagogical practice. These findings highlight the potential of action research as a form of professional development and its application in establishing teacher professional communities centred on reflection and innovation, aimed at enhancing educational practice and student learning.